Analisis dan Perancangan Halaman Website Simulasi Perakitan Sepeda - Albert Cahyadi; Friska Natalia (ULTIMA InfoSys, 2015)
Recently, Bike shop only sells bicycle in full bike or you can build it with components that suit you at the shop. However, these days many customer needs e-commerce web so that potential customers or buyers can shop online for their custom build bike. But if they want to see how it built, they have to see it on the shop or see other builds. The main idea of this study is to make a custom build simulation for bicycle web application for bike shop so that potential buyers could do a simulation first before they buy a custom build bike so that they know what components that suits them and know the weight, price and etc. The objective of this study is to make the potential buyer easier to find a bike that suits their needs. The methodology of system design in this study is using Rapid Application Development Method because the method could made the process very fast and always interact with the bike shop owner so that the application right on track. The website application was built by using MySQL Database and PHP programming language. The website is divided into 2 parts, which are one for customer and one for admin for maintaining the app. In this study use Spinwarrior bike shop for the example of the website implementation Index Terms: Bicycle, custom build, simulation, PHP, website.